Monitoring dispatching system based on Port's Internet of Things - Duanfeng Liu; Xuli Han; Xinru Liu (Institute of Advanced Engineering and Science, 2013)
This paper proposes monitoring dispatching system solution based on the internet of things, which is through the analysis for port’s current situation, system components, operation process, communication protocol and safety alarm, etc. The system can fulfill real-time precise positioning monitoring and dispatching for port’s mobile terminals, and also fulfill real-time monitoring and effective management for the whole port. Eventually it can improve the total competitiveness of port by improving production efficiency of port, securing operation safety and decreasing production cost. DOI: http://dx.doi.org/10.11591/telkomnika.v11i1.1882